Faktor-Faktor Penentu Tingkat Ketahanan Pangan Petani Lahan Kecil pada Kelompok Tani di Kecamatan Siman Kabupaten Ponorogo - Aysah Putri Cahyani; Ika Septiana Windi Antari (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to evaluate the influence of farming experience, production quantity, and consumption expenditure on the food security of farming communities. Data were analyzed by the Partial Least Squares (PLS) method. Data were collected through questionnaires distributed to farming households across five villages in Siman: Pijeran, Jarak, Demangan, Ngabar and Madusari. Respondents were selected using a combination of cluster sampling and random sampling techniques, resulting in a total of 97 participants. Data analysis included validity testing, reliability testing, and hypothesis testing. The results of this study indicate an R-squared value of 0.703. This value indicates that farming experience, production effectiveness and food accessibility on food security of 70.3%. And the rest is influenced by variables outside the variables in this study. The novelty of this research lies in its model linking farming experience, production quantity and consumption expenditure to food security. Practically, the research provides a foundation for farmers and stakeholders to enhance farming skills, optimize agricultural production and manage consumption expenses more effectively in order to strengthen food security within farming communities.